Passive smoking assessed by salivary cotinine and self-report in relation to cause-specific mortality: 17-year follow-up of study participants in the UK Health and Lifestyle Survey. Issue 12 (19th August 2014) - Batty, G David; Gale, Catharine R; Jefferis, Barbara; Kvaavik, Elisabeth
Abstract : Background: Evidence that passive smoking is a risk factor for cardiovascular disease and selected cancers is largely derived from studies in which this exposure is self-reported. Objective assessment using biochemical techniques may yield a more accurate estimate of risk, although each approach has its strengths and weaknesses. We examined the association of salivary cotinine, a widely utilised biomarker for passive smoking, and self-reported passive smoking in the home, with mortality from all causes, cardiovascular disease and all cancers combined. Methods: In 1992, investigators on the UK Health and Lifestyle Survey collected data on salivary cotinine, self-reported smoking (direct and passive) and a range of covariates in 3731 men and women aged 25 years and over. Mortality was ascertained using linkage to national death records. Results: Analyses were based on 2523 individuals (1433 [57%] women) who classified themselves as non-smokers (never and former). Seventeen years of follow-up gave rise to 588 deaths (253 from cardiovascular disease and 146 from cancer). In men, adjusted hazard ratios (HR) for the association between cotinine levels (1.3–15.0 [high] vs ≤0.3 [low] ng/mL) and the various mortality outcomes were weak for total mortality (HR; 95% CI: 1.22; 0.91 to 1.64) and cardiovascular disease (1.25; 0.78 to 1.99) and absent for all cancers combined (1.10; 0.61 to 2.00). Corresponding associations were generally stronger when self-reported passive smoking (some vs none) was the exposure of interest: 1.53 (1.12 to 2.08), 1.88 (1.20 to 2.96) and 1.58 (0.85 to 2.93). The pattern of association for women in both sets of analyses was less consistent. Conclusions: In men in the present study, compared with our biochemical marker of passive smoking, cotinine, mortality was generally more consistently associated with self-reported passive smoking.